Genotyping via Sequence Related Amplified Polymorphism Markers in Fusarium culmorum - Işıl Melis Zümrüt; Berna Tunalı; Bayram Kansu; Gülşen Uz; Emre Yörük; Fatih Ölmez; Ayşegül Sarıkaya (Turkish Journal of Agriculture: Food Science and Technology)
Fusarium culmorum is predominating causal agent of head blight (HB) and root rot (RR) in cereals worldwide. Since F. culmorum has a great level of genetic diversity and the parasexual stage is assumed for this phytopathogen, characterization of isolates from different regions is significant step in food safety and controlling the HB. In this study, it was aimed to characterize totally 37 F. culmorum isolates from Turkey via sequence related amplified polymorphism (SRAP) marker based genotyping. MAT-1/MAT-2 type assay was also used in order to reveal intraspecific variation in F. culmorum. MAT-1 and MAT-2 specific primer pairs for mating assays resulted in 210 and 260 bp bands, respectively. 11 of isolates were belonged to MAT-1 type whereas 19 samples were of MAT-2. Remaining 7 samples yielded both amplicons. Totally 9 SRAP primer sets yielded amplicons from all isolates. Genetic similarity values were ranged from 39 to 94.7%. Total band number was 127 and PCR product sizes were in the range of 0.1-2.5 kb. Amplicon numbers for individuals were ranged from 1 to 16. According to data obtained from current study, SRAP based genotyping is powerful tool for supporting the data obtained from investigations including phenotypic and agro-ecological characteristics. Findings showed that SRAP-based markers could be useful in F. culmorum characterization.